Stretching exercises for low back pain among dump truck operators in Indonesia - Oktarina, Astrid; Kekalih, Aria; Mirtha, Listya; Jason, Jason (International Journal of Occupational Safety and Health, 2025)
Introduction: Dump truck operators are at a greater risk of developing low back pain due to their occupational exposures. This study aimed to determine the effect of stretching exercises, especially pain intensity and flexibility, on low back pain among dump truck operators.Methods: A non-randomized controlled study with a pretest-posttest control group design was conducted, involving 76 dump truck operators with low back pain. A total of 38 operators were assigned for the control and intervention groups through purposive sampling. The control group only received an educational video for low back pain prevention, while the intervention group received an educational video with additional low back stretching exercises. Pain intensity and flexibility were assessed at baseline and weekly using the Numeric Rating Scale and the V-Sit and Reach Test. The collected data were analyzed using univariate, bivariate, and general linear models.Results: At the end of the intervention, a significant difference was found in pain intensity and flexibility between the control and intervention groups (p0.05).Conclusion: Low back stretching exercises can significantly reduce pain intensity and increase flexibility in low back pain. Dump truck operators or heavy equipment operators with low back pain should routinely do low back stretching exercises.